Supercommunicators : how to unlock the secret language of connection - Duhigg, Charles (Random House, 2024)
"We all know people who seem capable of connecting with almost anyone. They are the ones we turn to for advice, the ones who ask deep questions but also seem to hear what we are trying to say. What do they know about conversation that makes them so special? And what can they tell us about how communication really works? Supercommunicators, Charles Duhigg argues, understand--some by intuition, some by hard-won experience--that there is a science to how human beings connect through words. They understand that whenever we speak, we're actually participating in one of three distinct conversations: What is this really about? How do we feel? And who are we? They know the importance of recognizing--and then matching--each kind of conversation, and how to hear the complex emotions, subtle negotiations and hidden beliefs that color and inform everything we say. Our pasts, our values, our affiliations-our identities-shape every discussion we have, from who will pick up the kids to how we want to be treated at work"--